Policy Implementation Regarding Regional Waste TPA of Southwest Sumba Regency (Study at Southwest Sumba District Environmental Service) - Bulu, Novrianus Dede; Rifa’i, Muhammad; Suprojo, Agung (Journal of Social Research, 2023)
Researchers conducted research at the Southwest Sumba Regency Environmental Service. This research aims to determine the implementation of government policy in the provision of regional waste final disposal sites in Southwest Sumba Regency along with the inhibiting factors. This research method is qualitative, with data collection techniques using observation, interviews, and documentation. The results of the research show that: (1) the implementation of the Southwest Sumba Regency Regional Regulation policy Number 12 of 2019 concerning Final Disposal Sites for regional waste in Southwest Sumba Regency has not been implemented, this is due to the communication and socialization aspect of reducing regional waste. Consistency is also still minimal because there have been no firm efforts to implement administrative sanctions for business actors who do not pay fees or people who throw rubbish at illegal waste dumping sites. Based on the research results, most of the human resources implementing this policy, especially supervisors, only have a bachelor's degree or equivalent at the Environmental Service of Southwest Sumba Regency. Limited budgets make it difficult to procure machines for waste recycling, considering that the price per unit is expensive and it is not yet possible to provide them to villages, sub-districts, and the, entire community in Southwest Sumba Regency. Facilities and infrastructure are also limited, as many tools are in a damaged condition. Temporary disposal sites in several sub-districts have limited waste capacity. In terms of organizational structure, there are Standard Operating Procedures related to the provision of Regional Waste Final Disposal Sites and fragmentation involving the Southwest Sumba Regency Environmental Service. (2) Factors inhibiting the implementation of policies regarding final waste disposal sites in Southwest Sumba Regency, low public awareness of waste disposal, lack of firmness in implementing sanctions, lack of human resources, and budget limitations.